The Role of Supervisory Support and Life Balance Work in Increasing Organizational Citizenship Behavior: Study at Hotel Employees in Malang - Fiernaningsih, Nilawati (JPAS (Journal of Public Administration Studies), 2019)
The purpose of this study was to examine the effect of supervisory support on work life balance and organizational citizenship behavior. Data was collected from 209 five-star hotels and four-star hotels staff in Malang, East Java, Indonesia, using a questionnaire. Data was analyzed using GeSCA. The research findings show that supervisory support has a significant effect on work life balance, but supervisory support does not have a significant direct effect on organizational citizenship behavior. Meanwhile work life balance has a significant effect on organizational citizenship behavior. These findings provide insight to managers that employees need emotional support and instrumental so that they can balance work life with their personal lives. A good life balance work will foster organizational citizenship behavior that has an important role in improving the performance and competitiveness of the company.